2013
DOI: 10.2166/wst.2013.364
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance of hybrid constructed wetland systems for high-content wastewater treatment in the cold climate of Hokkaido, northern Japan

Abstract: The performance of six multistage hybrid constructed wetland systems was evaluated. The systems were designed to treat four kinds of high-content wastewater: dairy wastewater (three systems, average inflow content 2,400-5,000 mg·COD l(-1), 3-6 years of operation); pig farm wastewater, including liquid food washing wastewater (one system, 9,500 mg·COD l(-1), 3 years); potato starch processing wastewater (one system, 20,000-60,000 mg·COD l(-1), 3 years); and wastewater containing pig farm swine urine (one system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 13 publications
(24 reference statements)
0
3
0
1
Order By: Relevance
“…However, the field experience has indicated that plants can grow well and filtration bed does not freeze in high altitude locations (Navara, 1996;Merlin et al, 2002;Züst and Schönborn, 2003). This fact was also observed under northern latitude conditions such as in USA (Minnesota, Vermont, California), Norway, Canada or Northern Japan (e.g., Reuter et al, 1992;Kadlec et al, 2003;Mander and Jenssen, 2003;Muňoz et al, 2006;Giaever, 2003;McCarey et al, 2004;Yates et al, 2012;Kato et al, 2013).…”
Section: Introductionmentioning
confidence: 79%
“…However, the field experience has indicated that plants can grow well and filtration bed does not freeze in high altitude locations (Navara, 1996;Merlin et al, 2002;Züst and Schönborn, 2003). This fact was also observed under northern latitude conditions such as in USA (Minnesota, Vermont, California), Norway, Canada or Northern Japan (e.g., Reuter et al, 1992;Kadlec et al, 2003;Mander and Jenssen, 2003;Muňoz et al, 2006;Giaever, 2003;McCarey et al, 2004;Yates et al, 2012;Kato et al, 2013).…”
Section: Introductionmentioning
confidence: 79%
“…In Japan, multistage HSSF systems were designed to treat DWW under cold climate conditions. Researchers found high removal rates for COD RE (93-96.00%) [55]. In southern Europe, in various studies [12,[27][28][29][31][32][33], the authors reported average values of BOD 5 RE ranging between 70% and 94% depending on various factors, such as the size of the CW and the wastewater pretreatment.…”
Section: Monitoring and Pollutants Removal Efficiency Of The Hssfs Cwmentioning
confidence: 99%
“…However, the wastewater removal effect of major pollution in a constructed wetland would decrease in quite a few cold districts [9][10]. Therefore, some methods have been applied for solving the bottleneck problems [11].…”
Section: Introductionmentioning
confidence: 99%